2005
DOI: 10.1016/j.jacc.2004.12.077
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Activity on Serum C-Reactive Protein and Inflammatory Markers

Abstract: Physical activity is associated with a reduced incidence of coronary disease, but the mechanisms mediating this effect are not defined. There has been considerable recent interest in inflammation in the pathogenesis of cardiovascular disease. Some of the beneficial role of physical activity may result from its effects on the inflammatory process. We searched PubMed for articles published between 1975 through May 2004 using the terms exercise, physical activity, or physical fitness combined with C-reactive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
729
11
26

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 949 publications
(807 citation statements)
references
References 63 publications
41
729
11
26
Order By: Relevance
“…Long-term endurance training, as well as a sedentary lifestyle, 358 increase chronic systemic inflammation, 359 which in turn could also facilitate AF. 360 Studies show that moderate physical activity might reduce inflammatory markers.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…Long-term endurance training, as well as a sedentary lifestyle, 358 increase chronic systemic inflammation, 359 which in turn could also facilitate AF. 360 Studies show that moderate physical activity might reduce inflammatory markers.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…Of interest, it has been shown that activity of nuclear factor kappa B (NF-B), a transcription factor that controls many proinflammatory genes, increases with aging (15,16). Interestingly, participation in regular physical activity lowers CRP, and IL-6 levels (17,18). Importantly, chronic systemic inflammation is related to several aging-related diseases, including coronary heart disease and stroke, diabetes mellitus, Alzheimer's disease, and several autoimmune disorders, such as lupus, RA, and Sjogren's syndrome.…”
Section: Immunosenescence and Autoimmunitymentioning
confidence: 99%
“…A positive correlation between physical activity level of an individual and fibrinolysis time was reported in the literature [22,23]. The beneficial effect of regular physical activity is due to improvements in endothelial functions, endothelial progenitor cell activation and mobilization along with activity dependent release of muscle derived cytokines or leptins [24].…”
Section: Discussionmentioning
confidence: 89%